Factors associated with non-responsible self-medication in Peru - Pari-Olarte, Josefa Bertha (2021)
Introduction: Non-responsible self-medication leads to low effectiveness and insecurity in treatments, damage of health and patient dissatisfaction. Objective: To identify factors associated with non-responsible self-medication in the Peruvian population. Material and Methods: An analytical cross-sectional study was conducted based on the secondary analysis of the National Survey of Users Satisfaction in Health performed in Peru in 2016. It included 3849 users of pharmaceutical establishments. Chi-square statistic with p-value, crude odds ratio (cOR) and adjusted odds ratio (aOR) with its 95% confidence interval (95% CI) were calculated. Results: When the dispenser of the medicine did not request the prescription from the user, the risk of non-responsible self-medication was very high (aOR=29.057). Additionally, going to the pharmaceutical establishment to ask for advice (aOR=1.884), eventual consumption of the purchased medicine (aOR=1.925), less than five minutes delay in purchasing medicine (aOR=1.587) and being male (aOR=1.321) were also risk factors. The proximity of the pharmaceutical store to health services from the first and second level of health care also acted as a risk factor (cOR=1.340 and 1.652, respectively). Conclusion: The lack of request for prescription in the pharmaceutical establishment was the main risk factor for non-responsible self-medication.